(untitled) - Page, C. L. (New York, 2007)
Concrete and other cement-based composites are by far the most widely used man-made construction materials in the world. However major problems of infrastructure deterioration have been caused by unanticipated premature degradation of these materials. This book will provide an up-to-date review of several of the main forms of degradation, examining what is known about their causes and control. Trends in modelling and prediction of service-lives will also be examined. CONTENTS Physical and chemical characteristics of cement-based materials; Dimensional stability and cracking processes; Chemical degradation of concrete; Corrosion and protection of reinforcing steel; Techniques for remedial treatment of reinforcement corrosion; Degradation phenomena in prestressed concrete; Aggregate instability problems; Freeze-thaw and deicer-induced degradation; Degradation of fibre-reinforced cement composites; Degradation of polymer-cement composites and related material.
Keywords: Cement,Xi măng,Concrete